Fundamental ideas in cosmology : scientific, philosophical and sociological critical perspectives - López-Corredoira. Martín (IOP (Series). Release 22., 2022)
This book examines the world of cosmological research, providing an in-depth critical review of the research associated with challenges to the standard Big Bang scenario. It includes studies that are apparently at odds with the current standard Lambda-CDM model, providing examples of alternative theories, tests and problems with the standard model, and a discussion on the philosophy and sociology of cosmology.